Innovative Strategies in Math Education: The Impact of PBL and TaRL on Concept Mastery and Classroom Dynamics - Sriyanti Mustafa; Nur Ilmi; Suliati Suliati (Jurnal VARIDIKA, 2024)
In scrutinizing the amalgamation of Problem-Based Learning (PBL) and Teaching at the Right Level (TaRL) approach within mathematics pedagogy, extant scholarship scarcely offers a holistic evaluation of their synergistic efficacy. Prior research predominantly accentuates scholastic outcomes, frequently neglecting the ramifications of these models on classroom dynamics, including the nuances of student-teacher interactions and student engagement and participation levels. This study probes the integration of PBL and TaRL models to augment students' comprehension of mathematical principles, employing a mixed-methods research design encompassing qualitative and quantitative methodologies. The investigation centered on seventh-grade students in junior high school, utilizing test instruments to evaluate mathematical comprehension and observational protocols to document student and teacher engagement for enriched insights. Comprehensive qualitative and quantitative data analyses were executed. The findings disclosed significant advancements in students' grasp of mathematical concepts, with observations revealing heightened student engagement and more favorable teacher-student interactions. Statistical analyses evidenced substantial disparities between pre-test and post-test scores (p < 0.05). The results proffer recommendations and pragmatic implications for enhancing mathematics education, underscoring the imperative for teacher professional development in deploying this integrative pedagogical model to elevate the quality of mathematics instruction at the secondary school echelon.